Three-Dimensional Computer Model of Benign Paroxysmal Positional Vertigo in the Semi-Circular Canal - Milosevic, Zarko; Saveljic, Igor; Nikolic, Dalibor; Zdravkovic, Nebojsa; Filipovic, Nenad; Vidanovic, Neda (EAI Endorsed Transactions on Pervasive Health and Technology, 2018)
Benign Paroxysmal Positional Vertigo (BPPV) is the most common vestibular disorder. In this paper we tried to investigate a model of the semi-circular canal (SCC) with parametrically defined dimension and full 3D three SCC from patient-specific 3D reconstruction. Full Navier-Stokes equations and continuity equations are used for fluid domain with Arbitrary-Lagrangian Eulerian (ALE) formulation for mesh motion. Fluid-structure interaction for fluid coupling with cupula deformation is used. Particle tracking algorithm has been used for particle motion. Velocity distribution, shear stress and force from endolymph side are presented for one parametric SCC and three patient-specific SCC. All models are used for correlation with the same experimental protocols with head moving and nystagmus eye tracking.
Keywords: semi-circular canals; sedimenting particle; BPPV; biomechanical model; fluid-structure interaction